2014
DOI: 10.1111/pirs.12025
|View full text |Cite
|
Sign up to set email alerts
|

The sources of the urban wage premium by worker skills: Spatial sorting or agglomeration economies?

Abstract: Abstract. We estimate the respective importance of spatial sorting and agglomeration economies in explaining the urban wage premium for workers with different sets of skills. Sorting is the main source of the wage premium. Agglomeration economies are in general small, but are larger for workers with skills associated with non-routine job tasks. They also appear to involve human capital accumulation, as evidenced by the change in the wage of workers moving away from denser regions. For workers with routine jobs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
75
0
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 79 publications
(88 citation statements)
references
References 42 publications
11
75
0
2
Order By: Relevance
“…When also controlling for unobservable characteristics of workers (columns 4-6, Table 3), the city effects are still increasing in education level, from 3.2% to 6%. Hence, consistent with most US studies as well as the Swedish study by Andersson et al (2014), we find that the city effect is increasing in education level / skills. This result survives when worker fixed effects are included, but educational differences become smaller.…”
Section: Static Agglomeration Effects Across Education Groupssupporting
confidence: 78%
See 1 more Smart Citation
“…When also controlling for unobservable characteristics of workers (columns 4-6, Table 3), the city effects are still increasing in education level, from 3.2% to 6%. Hence, consistent with most US studies as well as the Swedish study by Andersson et al (2014), we find that the city effect is increasing in education level / skills. This result survives when worker fixed effects are included, but educational differences become smaller.…”
Section: Static Agglomeration Effects Across Education Groupssupporting
confidence: 78%
“…Exceptions are Adamson et al (2004) who find a nonlinear relation between the urban wage premium and education level, and Lee (2010) who finds that the urban wage premium is negative for high-skilled health workers and positive for less skilled health workers. A Swedish study based on panel data of all private sector workers finds that the urban wage premium is largest for workers in occupations that demand non-routine tasks (Andersson et al, 2014), whereas, in Italy, return to higher education seems to be negatively correlated with regional population size (Di Addario and Patacchini, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…It is well established in the literature that large core regions tend to host significant research and development (R&D) activities, and are also more geared toward entrepreneurialism in knowledge-intensive and innovation activities (e.g., Duranton andPuga 2001, 2005). Recent studies that focus on worker skills also show that larger cities and core regions are not only more intensive in, but also more rewarding for, skills associated with innovation activities such as cognitive skills related to problem solving and creativity (Bacolod, Blum, and Strange 2009;Andersson, Klaesson, and Larsson 2014). Against this backdrop, core regions with a higher density of knowledge-intensive activities are likely to be in a better position to develop, for the region, truly new industries and to break from their past industry structure.…”
Section: Introductionmentioning
confidence: 99%
“…Burger et al (2010) found different effects of agglomeration forces across geographic levels in the Netherlands. In Andersson et al (2014), Swedish employment data is used at a 1×1 km and 250×250 m sized grid. Furthermore, unit observation size and some of its features may be correlated and hence, estimates may be biased.…”
Section: Introductionmentioning
confidence: 99%